The Influence Of Competence And Information Technology On Performance in Nurses in The Inpatient Installation Of Sekayu Hospital - Farida Yazid (Jurnal Syntax Transformation, 2023)
Research that uses a case study qualitative method and the chosen research subject is the government can provide a deeper understanding of the importance of communication development through information and communication technology in the era of globalization, navigation and decentralization. Some of the findings resulting from this research are as follows: The Importance of Development Communication through ICT: Research shows that effective development communication by utilizing ICT media, especially through e-Government has a positive impact on improving good, fast and responsive public services. The use of this technology allows local governments to interact directly with the community, convey information about development programs, and facilitate active community participation in the development process. In addition, budget transparency and development programs are also important factors in building public trust in the government.